Securitization and Mortgage Renegotiation: Evidence from the Great Depression - Ghent, Andra C. (Review of Financial Studies, 2011)
We use loan-level data from the New York City metropolitan area to examine the extent to which lenders attempted to prevent foreclosures with concessionary modifications during the Great Depression. We find no principal forgiveness in the sample and only a handful of concessionary mortgage modifications of other types. Far more mortgages terminated through foreclosure than received any sort of concessionary modification. The results indicate that there are significant impediments to renegotiation of residential mortgages beyond securitization. As such, less renegotiation seems unlikely to be a major cost of securitization of residential mortgages. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.